ALGORITMO DE OTIMIZAÇÃO PARA VISUALIZAÇÃO DE MODELOS URBANOS COM BANCO DE DADOS GEOGRÁFICOS - Serrão, Ronald Silva (2008)
Virtual Reality Systems have been used in diverse areas in recent years, providing many benefits. A class of these systems is for visualization and manipulation of virtual urban models, that can be used for urban planning, architectural, visualization and games. This work presents the conception and development of an optimized algorithm for urban virtual models visualization with cache, based in Geographical Database. The proposed cache strategy provides a good performance for urban virtual models walktrough. To test the proposed algorithm it was built an urban virtual model based on São Luis historical town.